Modeling of CFRP strengthened RC beams using the SNSM technique, proposed as an alternative to NSM and EBR techniques - Boulebd Adel; Ferhoune Noureddine; Boukhezar Mohcene; Habib Abdelhak Mesbah (Fracture and Structural Integrity)
In this paper, an analytical and numerical study in finite element by the ABAQUS software was conducted. The goal of this work is to study the bending behaviour of reinforced concrete beams strengthened with the side near surface mounted technique. This technique is proposed as an alternative to overcome the unpredictable failure mode by the strengthening detachment resulting from the external bonded strengthening technique. Also, to avoid the failure mode by separation of the concrete cover ensuing from the near surface mounted technique. Moreover, a comparison between the behaviour of the three techniques, the effect of the quantity of strengthening as well as a validation of the results with the literature were presented. The results of this study show that numerical and analytical models can be used to predict the behaviour of reinforced concrete beams strengthened according to the three techniques. In addition, a clear improvement of the strengthened beams bending capacity is noticed. Lastly, the side near surface mounted technique preserves the ductility of the reinforced concrete beams modeled and therefore provides a better failure mode.